If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 5 = 317 Reorder the terms: 5 + 6x = 317 Solving 5 + 6x = 317 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 6x = 317 + -5 Combine like terms: 5 + -5 = 0 0 + 6x = 317 + -5 6x = 317 + -5 Combine like terms: 317 + -5 = 312 6x = 312 Divide each side by '6'. x = 52 Simplifying x = 52
| 8x^2+7xy-y^2=8 | | -2y+4=10 | | 3x-7/9x^2-49 | | 0=7+-8y+y^2 | | 118-4/9 | | 2x+7=1-6(x-5) | | 0=-8y+y+y^2 | | 7/8-17/24 | | 0=Y^2+-8y+7 | | 3+x=9y | | N^2-18=3n | | 196=pir^2(r)(s) | | 1/6k | | 4c+1-7c= | | 13.99(x-12)=50 | | 5x-10+3=7x-9 | | 0=y^2-12y+27 | | 4c*1+-7c= | | b=arn-1 | | -(-x)-3(-2x)+3(-2+x)=-(x-5) | | 4c+(-7c)= | | 8a^2=16a | | 30x*6/30=12,5 | | -m^2=-125 | | 2x/2x^2+6x | | 4c+1(7c)= | | 4c-7c= | | x/10=0,1 | | 20/3+4 | | f(2)=24-2(7) | | 0=y^2-2y-8 | | h(x)=8x^2-4x+1 |